Power against random expenditure allocation for revealed preference tests - Per Hjertstrand (Research Institute of Industrial Economics (IFN), 2019)
This paper proposes new power indices for revealed preference tests. The indices are based on a model of irrational consumption behavior where the consumer randomly allocates a certain fraction of expenditure. The methods allow a researcher to trace out the entire power curve against random expenditure allocation. The power indices are illustrated on altruistic choices in experimental data.
Keywords: C14; D12; 330; GARP; Power; Revealed preference